Chemical Papers - Polakovic, Milan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Chemical Papers is a peer-reviewed, international journal devoted to basic and applied chemical research. It has a broad scope covering the chemical sciences, but favors interdisciplinary research and studies that bring chemistry together with other disciplines. Fields of interest to the journal include: - analytical chemistry, - (bio)catalysis, - biochemistry, - chemical (bio)technology, - (bio)chemical engineering, - chemical physics, - drug chemistry, - food chemistry, - environmental chemistry, - inorganic chemistry, - macromolecular chemistry, - materials chemistry, - mathematical chemistry, - medical and pharmaceutical chemistry, - nanochemistry, - organic chemistry, - and physical chemistry. Chemical Papers publishes original full-length papers, short communications, and reviews. Short communications may be processed and published faster when urgent publication is substantiated. Longer review articles must be submitted with previous consent from the Editor-in-Chief, but this is not necessary for shorter reviews.
Keywords: Chemistry; Biotechnology; Chemical engineering; Medicinal chemistry; Biochemistry; Materials science; Chemistry/Food Science, general; Industrial Chemistry/Chemical Engineering; Biochemistry, general; Medicinal Chemistry; Materials Science, general; Biotechnology